A Review of the Molecular Understanding of the Mpox Virus (MPXV): Genomics, Immune Evasion, and Therapeutic Targets - Edgar Manuel Cambaza (Zoonotic Diseases)
The Mpox virus (MPXV), a zoonotic pathogen from the Orthopoxvirus genus, has emerged as a significant global public health concern, especially after the unprecedented outbreak in 2022. This review synthesizes the MPXV’s molecular features, focusing on its genomic structure, replication mechanisms, immune evasion strategies, and implications for diagnostics and therapeutics. The study examines the virus’s genomic organization utilizing recent peer-reviewed literature, highlighting essential genes like OPG027 and D1L, which contribute to host adaptation, increased transmissibility, and immune evasion. Advances in molecular diagnostics, including real-time PCR and genome sequencing, are reviewed, emphasizing their critical role in outbreak monitoring and control. However, challenges persist, such as diagnostic limitations in resource-constrained settings and the lack of targeted vaccines and antivirals. This review discusses new antiviral candidates, confirmed through computational and in vitro techniques, identifying thymidine kinase and VP39 as key therapeutic targets. Emphasizing the need for genomic surveillance to track adaptive evolution, results show that particular mutations, such as in the OPG027 and D1L genes, increase the transmissibility and immune evasion of the MPXV. These molecular revelations highlight the urgent necessity for better diagnostics catered towards addressing present constraints and developing focused treatments that reduce the effect of the virus. This study emphasizes how these results underscore the need for combined public health plans to handle the changing MPXV epidemiology properly.